(untitled) (Research, Society and Development, 2022)
Drug therapy is an integral part of the aged care plan, and prescribing is a difficult and challenging process. Investigating the prescription of the aged is a practice recommended as a tool in the evaluation of the quality of the health service, since drug treatment is an essential element of clinical care for the aged, and the optimization of prescription is necessary, as it has become a worldwide important health problem. The present study aims to present and discuss the quality indicators of prescription in the aged and the use of instruments and measures as strategies for their appropriate use in the health system. The method used was the narrative review of the literature, through works already published, found in databases in Portuguese and English, to collaborate with the continuing education of health professionals and provide the rational and safe use of drug therapy. In view of the data presented, it is essential to promote a quality and adequate prescription so that the aged can have a better quality of life so that they can live as long as possible in their homes with health, autonomy and independence.